A cohort-based comprehensive characterization of different patterns of very short-term, within-visit, blood pressure variability. Issue 3 (June 2020) - Papaioannou, Theodore G.; Protogerou, Athanase D.; Stamatelopoulos, Kimon S.; Alexandraki, Krystallenia I.; Vrachatis, Dimitrios; Argyris, Antonios; Papaioannou, Vasilios; Vavuranakis, Manolis; Stefanadis, Christodoulos; Tousoulis, Dimitrios
Abstract : Aim: To characterize different patterns of variability of three repeated within-visit blood pressure (BP) readings and to determine the prevalence of specific variation trends in systolic (SBP), diastolic (DBP) blood pressure and pulse pressure (PP). Methods: Data from 53 737 subjects from the National Health and Nutrition Examination Survey were analyzed. In each subject, three consecutive BP measurements were performed with a minimum time-interval of at least 30 s. We propose three patterns of within-visit BP variability (separately for SBP, DBP and PP): (1) increasing trend (BP3  > BP2  > BP1 ); (2) decreasing trend (BP1  > BP2  > BP3 ) and (3) no trend (BP3  ≈ BP2  ≈ BP1 ). A threshold of minimum change (ΔP > 3 mmHg) between BP1 -BP2 and BP2 -BP3 was also applied as a prerequisite for the definition of these trends. Results: An increasing trend was observed among three consecutive measurements of SBP, DBP and PP in 7.4, 10.4 and 10.2%, respectively. When a minimum threshold of 3 mmHg was set the respective increasing trends were observed in 1.8, 2.9 and 4.4%, respectively. There was a higher prevalence of decreasing trend within three consecutive SBP, DBP and PP readings: 17, 13.1 and 16.2%, respectively, whereas using a threshold of ΔP >3 mmHg the respective prevalence was 6.3, 4.1 and 7.7%. A maximum absolute difference >10 mmHg within triplicate of SBP/DBP/PP readings was observed in 12.9, 13 and 29.4%, respectively. In the era of personalized medicine, these patterns are well worth further investigation concerning their pathophysiologic and clinical relevance.